2007
DOI: 10.1002/art.22714
|View full text |Cite
|
Sign up to set email alerts
|

Activation of invariant natural killer T cells by synthetic glycolipid ligands suppresses autoantibody‐induced arthritis

Abstract: Objective. Stimulation of invariant natural killer T (iNKT) cells with SGL-S23, a novel synthetic glycolipid analog of ␣-galactosylceramide with an elongated sphingosine chain, has been shown to strongly suppress K/BxN serum transfer arthritis. This study was designed to evaluate the protective effects of SGL-S23 in an effector phase of arthritis.Methods. To induce arthritis, C57BL/6 mice were injected with 150 l of serum from K/BxN mice (KRN TCR-transgenic mice crossed with nonobese diabetic mice). Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 48 publications
1
23
0
1
Order By: Relevance
“…Similarly, in vivo injection of SGL-S23 resulted in weaker IFN-serum responses. In keeping with the known essential role played by mast cells in the development of arthritis in the K/BxN serum transfer model, Kaieda et al (2007) showed an elevation in serum histamine level five minutes after serum injection, abolished by pre-treatment with low-dose IFN-. SGL-S23 also suppressed histamine release, and more effectively so than α-GalCer or high dose IFN-.…”
Section: Manipulating Inkt Cells For Clinical Benefitsupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly, in vivo injection of SGL-S23 resulted in weaker IFN-serum responses. In keeping with the known essential role played by mast cells in the development of arthritis in the K/BxN serum transfer model, Kaieda et al (2007) showed an elevation in serum histamine level five minutes after serum injection, abolished by pre-treatment with low-dose IFN-. SGL-S23 also suppressed histamine release, and more effectively so than α-GalCer or high dose IFN-.…”
Section: Manipulating Inkt Cells For Clinical Benefitsupporting
confidence: 75%
“…Screening a panel of analogs of α-GalCer for the ability to suppress the development of arthritis in a B6 model of K/BxN serum transfer-induced arthritis, Kaieda et al (2007) found SGL-S23, an analog with a 5-carbon longer sphingosine base that could inhibit clinical and histological disease severity to a greater degree than α-GalCer by i.p. administration on days 0, 3 and 7.…”
Section: Manipulating Inkt Cells For Clinical Benefitmentioning
confidence: 99%
“…iNKT cells show a remarkable functional diversity, and elicit varying and opposing immune functions. On the one hand, they actively induce T-cell tolerance and are crucial for the prevention of autoimmune diseases in pre-clinical models of MS [16,17], type 1 diabetes [18,19], systemic lupus erythematosus [20], myasthenia gravis [21] and rheumatoid arthritis [22,23]. On the other hand, iNKT cells participate in the innate immune response to promote antimicrobial [24][25][26] and antitumor [27][28][29][30] immunity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of ␣-GalCer is limited by the opposing effects of the Th1 and Th2 cytokines induced by this glycolipid. In order to develop selective Th1 or Th2 activators, many ␣-GalCer analogs were synthesized (1,3,5,8,12,14,21,34,36), and their immune-modulating activities were shown to be related to the affinity of binding to CD1d (8). Recent studies using a CD1d array established that the secretion of IFN-␥ and IL-4 by NKT cells is determined by the binding of ␣-GalCer analogs to CD1d (21), and a higher affinity for CD1d would shift the cytokine release profile toward a stronger Th1 response (3,21).…”
mentioning
confidence: 99%